Culture, Peace and Development: The Case Study of West Pokot County, Kenya - Mose, Wyclife O.; Nyambura, Salome (Machakos University, 2018)
Violent conflict has been experienced in West Pokot County for decades. This county is the home of pastoral communities whose livelihood entirely depended on a cow for centuries. As such, conflicts in this region rotated around a cow. This study interrogated extent to which cultural practices have contributed to peace and development of the region. The study applied case study design situated within the qualitative tradition. Women, men, youth, NGOs officials, and representative from all levels of governments provided information. The study found that cultural practices such as songs encouraged conflict and peace in the one hand. On the other, some aspects of cultural practices have sustained lives and promoted growth of prosperity of people. The study recommended that the government, nongovernmental organizations and the community to initiate regular dialogue meetings, peace tours, cultural events and sports for peace to create more awareness on peace, benefits of peace, and increase levels of interactions among the warring communities in a bid to spur social-economic development of people. Key words: Culture, Peace, Development, West Pokot, Kenya
Keywords: Culture; West Pokot